Competence, Motivation, and Organizational Commitment on Job Satisfaction and Employee Performance at Bank Sinarmas Pekanbaru Riau Branch - Diana Gazali; Harry Patuan Panjaitan; Teddy Chandra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This research aims to test the influence of competence, motivation, and organizational commitment on job satisfaction and employee performance at PT Bank Sinarmas Tbk Pekanbaru Riau Branch. The phenomenon that occurs is that every year there are still employees who get poor employee performance assessments. The Structural Equation Modeling method is used to test the effect of independent variables on dependent variables. The samples used in this study were all permanent employees at PT Bank Sinarmas Tbk Pekanbaru Riau Branch. The results showed that the variables of competence, motivation, and organizational commitment had no significant effect on job satisfaction. The variables of competence, motivation, organizational commitment, and job satisfaction are insignificant to employee performance.